2019
DOI: 10.21307/aoj-2020-043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of treatment risks and the quality of information contained within the websites of specialist orthodontists

Abstract: Objective To evaluate the treatment risks and the quality of information contained within the websites of specialist orthodontists in Australia. Methods The term ‘specialist orthodontic practice’ was entered into three internet search engines. Websites satisfying inclusion and exclusion criteria were evaluated for orthodontic treatment risk information against nine common treatment risks. For website reliability and quality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The public is increasingly accessing online resources in searches for health information. 36 Of concern and in addition, the content uploaded onto websites is largely unregulated which further underlines the importance of studies to assess the quality and readability of the information. 24 The findings of the present study indicated that the online information related to AO was highly variable as the readability scores were below the recommended levels for written health information.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The public is increasingly accessing online resources in searches for health information. 36 Of concern and in addition, the content uploaded onto websites is largely unregulated which further underlines the importance of studies to assess the quality and readability of the information. 24 The findings of the present study indicated that the online information related to AO was highly variable as the readability scores were below the recommended levels for written health information.…”
Section: Discussionmentioning
confidence: 99%
“…2 Multi-stakeholder effort is required to ensure that clearly written, unbiased, reliable and evidenced-based information is provided. 24,36,43 To enable this, the healthcare professions could work collaboratively to ensure that authors of websites strive to include a 'seal of reliability' on their websites (such as the HONcode seal), and to ensure that the public are aware of its existence and its meaning. A remedial approach would be for professional dental societies to develop freely available online information websites that satisfy the criteria for high-quality information, and to which search engines and websites can provide a link.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations